Research on the purchase intention of museum digital cultural and creative products based on value adoption model - Mengen Gu; Tongtong Zhao (Scientific Reports)
Abstract Museum digital cultural and creative products rejuvenate ancient treasures and promote the development of cultural and creative industries. With the surge in purchases over the past few years, investigating the underlying factors has become a compelling question. Therefore, based on the Value-Based Adoption Model, this paper explores the factors and intrinsic mechanisms influencing consumers’ purchase decisions regarding these products. The collected data were analyzed using SPSS for preliminary analysis, and structural equation modeling was conducted using AMOS to test the research hypotheses. Results showed: (1) Perceived benefits positively influence purchase intention and value. (2) Perceived sacrifices negatively influence purchase intention and value. (3) Perceived value positively influences purchase intention and mediates the effects of perceived benefits and sacrifices. (4) Social influence positively moderates the relationship between perceived value and purchase intention. Specifically, entertainment experience, cultural experience, and perceived value positively influence purchase intention, while perceived cost and perceived risk negatively impact it. Based on these findings, developers should enhance product playability and cultural significance. Relevant departments should employ various strategies to reduce consumers’ cybersecurity risks and copyright issues during shopping while also minimizing selling costs to attract more consumer attention and purchases.